Assessing the Short-Term Efficacy and Safety of Guselkumab for Moderate-to-Severe Plaque Psoriasis: Meta-Analysis of Randomized Controlled Trials - Jing Yang; Zongming Wang; Xilin Zhang (Journal of Immunology Research)
Background. To investigate the efficacy and safety of guselkumab in the treatment of moderate-to-severe plaque psoriasis. Methods. A systematic review was undertaken to identify double-blind randomized controlled trials (RCTs). PubMed, Web of Science, Cochrane Library, EMBASE, and Google Scholar databases were searched before 1 March 2020. The odds ratios (ORs) with 95% confidence interval (CI) were calculated. All analyses were conducted with intention-to-treat basis. A range of sensitivity analyses was undertaken. Results. A total of 7 articles contained 1206 plaque psoriasis patients with guselkumab, 585 patients with placebo, and 1250 patients with adalimumab were included. The results indicated that guselkumab had better efficacy than placebo or adalimumab for Psoriasis Area and Severity Index score reductions from baseline of 75% (PASI 75) (OR=61.37, 95% CI=31.15 to 120.91; OR=3.08, 95% CI=2.35 to 4.06), Investigator’s Global Assessment scores of 0 or 1 (IGA 0/1) (OR=65.75, 95% CI=45.54 to 94.95; OR=2.79, 95% CI=2.17 to 3.59), and Dermatology Life Quality Index scores of 0 or 1 (DLQI 0/1) (OR=29.64, 95% CI=18.80 to 46.73; OR=1.86, 95% CI=1.50 to 2.31). The guselkumab had similar safety with placebo or adalimumab about the incidence of adverse events (AEs) (OR=1.05, 95% CI=0.86 to 1.29; OR=0.97, 95% CI=0.79 to 1.19) and serious adverse events (SAEs) (OR=1.03, 95% CI=0.47 to 2.27; OR=0.91, 95% CI=0.44 to 1.87). Meanwhile, there was no statistically significant association of infections and serious infections compared with the placebo or adalimumab group. The guselkumab was more effective and had the similar tolerance. Conclusion. The guselkumab had excellent efficacy and great safety in moderate-to-severe plaque psoriasis, but long-term safety remained to be determined.